Effect of Curing Current on Stiffness and Damping Properties of Magnetorheological Elastomers - Hapipi, Norhiwani; Mazlan, Saiful; Aziz, Siti; Ubaidillah, Ubaidillah; Mohamad, Norzilawati; Yazid, Izyan; Choi, Seung-Bok (http://dx.doi.org/10.31427/IJSTT.2018.1.2.3, 2018)
In this study, the viscoelastic effects of the magnetic field strength imposed for curing process on the stiffness and damping properties of magnetorheological elastomers (MREs) are experimentally investigated. In order to observe the effect, three different samples of MRE are fabricated by imposing curing current of 0.1 A, 0.3 A and 0.5 A which is equivalent to the magnetic field of 70 mT, 309 mT, and 345 mT, respectively. All samples consist of 30% silicone rubber and 70% carbonyl iron particles (CIPs) by weight percentages. After observing the morphological images via SEM, the dynamic performances of these samples, such as storage modulus and loss factor are evaluated and compared as a function of the magnetic field intensity or oscillation frequency. It is shown that the sample cured at 0.5A exhibits the highest storage modulus in the frequency domain. In addition, MR effects of three samples are identified, and it is found that the sample cured at 0.5A shows the highest absolute and relative MR effect.